2019
DOI: 10.1039/c9nj01311c
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated zirconia: an efficient catalyst for the Friedel–Crafts monoalkylation of resorcinol with methyl tertiary butyl ether to 4-tertiary butylresorcinol

Abstract: Sulfated zirconia (SZ) is an efficient and recyclable catalyst in the selective monoalkylation of resorcinol with MTBE to 4-tertiary butyl resorcinol at low temperature (60 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…After sulfidation, two peaks located at 182.1 eV and 184.5 eV were observed on the XPS Zr 3d spectrum (Figure 3a). They were characteristic of ZrO2 [36]. XPS also evidenced the success of the sulfidation process (Figure 3).…”
Section: Characterization Of the Mesostructured Zro 2 -Based Catalystmentioning
confidence: 84%
“…After sulfidation, two peaks located at 182.1 eV and 184.5 eV were observed on the XPS Zr 3d spectrum (Figure 3a). They were characteristic of ZrO2 [36]. XPS also evidenced the success of the sulfidation process (Figure 3).…”
Section: Characterization Of the Mesostructured Zro 2 -Based Catalystmentioning
confidence: 84%
“…XPS analysis of the survey profile revealed enriched amounts of C, O, N, and Fe on the BCs’ surface (Figure S3). The Zr peak was observed in two binding energies at approximately 182.64 eV (Zr 3d 5/2 ) and 185.45 eV (Zr 3d 3/2 ), which represented Zr-oxide , on the Zr–FeCl 3 B surface (Figure B). XPS survey analysis also confirmed the As 3d spectrum on the BC surface (Figure S4).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The XPS spectra revealed that the second peak produced at 185.45 eV in the Zr 3d 3/2 region corresponds to the Zr–O 2 , (Figure B). Lewis acid–base definition classified Zr to be more basic than Fe species (Fe 2+ or Fe 3+ ) which also enables Zr to function as a reductant.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, signals corresponding to S=O and titanium oxide were not clear in the spectra. To elucidate whether the acidic sites on the catalysts have Lewis acidic or Brønsted acidic nature, FT−IR analysis of pyridine‐absorbed samples was conducted using Nujol mull or KBr pellet methods [3a,18] . The catalysts were treated with pyridine at room temperature and then dried in vacuo before FT−IR analysis.…”
Section: Methodsmentioning
confidence: 99%